Naturaleza de la acción educativa (1998)
Beginning with the Aristotelian theory of the human action, an analysis of the educating action is made to show how education belongs to a genre of actions called practices or praxis in the Aristotelian tem, and in consequence. what has todo with its execution, falls into the practica1 reasoning ; yet its technological dimension belongs to the theoretical reasoning.